Streamlining pedagogical technologies in digital educational environment - A. Yu. Anisimov; A. N. Aleksakhin; S. A. Aleksakhina; L. S. Baytimerova (Вестник Северо-Кавказского федерального университета)
Introduction. The transition to a digital economy has a transformational impact on the social environment, including education. The effect of digitalization processes is observed in two directions: on the one hand, the need for personnel with digital skills and competencies is growing, on the other hand, remote and digital technologies are actively used in education. The result of the formation of a new technological structure is the creation and implementation of a qualitatively new educational environment in the digital space, which determines the relevance of adapting pedagogical technologies to the changed conditions for the development of the socio-economic system. The complexity of the process of adapting pedagogical technologies to the digital educational environment is due to the need to develop skills, competencies and skills in accordance with the needs of the formation of qualitatively new human capital.Goal. To summarize the accumulated experience of transforming pedagogical technologies, to develop an adaptive mechanism for their use in a digital educational environment.Materials and methods. The study is based on the use of general scientific methods in analyzing the empirical base and accumulated experience in the development and implementation of new pedagogical technologies in the context of the development of a digital educational environment and distance learning formats.Results and discussion. A consistent study of the process of adaptation of pedagogical technologies gives a comprehensive idea of the peculiarities of the formation and development of the digital educational environment, as well as its impact on the transformation of educational technologies. This approach made it possible to identify and characterize typical models of organizing the educational process using modern pedagogical technologies adapted to the needs of the digital economy. The key result of the study is the development of an adaptive mechanism for their use in a digital educational environment.Conclusion. In general, the adaptation of pedagogical technologies to modern socioeconomic conditions will not only improve the quality of the educational process in the context of digital transformation, but will also contribute to the development of the necessary and demanded professional competencies of the new generation of human capital.